2018
DOI: 10.1002/jper.17-0586
|View full text |Cite
|
Sign up to set email alerts
|

Validity of self‐reported periodontal measures, demographic characteristics, and systemic medical conditions

Abstract: Self-reported periodontal screening questions as well as demographic characteristics, smoking, and systemic medical conditions were significant predictors of periodontal disease, and they could be used as valid, economic, and practical measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 45 publications
3
20
1
Order By: Relevance
“…It was acknowledged that a single, self-reported item might not be accurate enough to discriminate between individuals with periodontal disease and those without it. Models combining both self-report measures and some demographic characteristics should provide more valid results [12,15,18]. Moreover, there is a great need to educate women in order to increase the perception about potential oral health changes during pregnancy as well as to raise the awareness regarding potential adverse pregnancy outcomes.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…It was acknowledged that a single, self-reported item might not be accurate enough to discriminate between individuals with periodontal disease and those without it. Models combining both self-report measures and some demographic characteristics should provide more valid results [12,15,18]. Moreover, there is a great need to educate women in order to increase the perception about potential oral health changes during pregnancy as well as to raise the awareness regarding potential adverse pregnancy outcomes.…”
Section: Plos Onementioning
confidence: 99%
“…However, due to the discrete symptoms intensity during the initial phases of development, periodontitis is hardly recognized by patients. An accessible, reliable, cost-effective, time-saving strategy to facilitate periodontal disease detection could be beneficial to guide the subjects toward specialized evaluation [7,12,15,17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-reported presence of tooth mobility was previously found to be a significant predictor of periodontitis with high specificity and low sensitivity across different epidemiological surveys and populations [12,68,69], and its degree was associated with advanced stages of the disease [20,70].…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] A number of studies have also investigated the validity of selfreported measures for periodontal diseases. [13][14][15][16][17][18][19][20][21][22][23] Some studies reported that a multivariable model containing sociodemographics as well as self-reported periodontal health-related question items was valid for the prediction of clinical periodontitis. [15][16][17][18][19] However, other studies conducted in various countries have demonstrated contrasting results.…”
Section: Introductionmentioning
confidence: 99%